Investigation of microstructure and corrosion behaviour of Malay Keris - Mukhtaruddin bin Musa (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Keris is one of the most prominent Malay heritage resulted from the greatest technological advancements in old Malay civilization. Not only functioning as a weapon, keris also symbolizes sovereignty, dignity and social status thus making it as one of the most desirable property for Malay to own. However, as time goes by, the role of keris changes and the demand for the keris is only restricted to the cultural ceremony. Besides, this scenario also seems to endanger the art of keris making especially in Malaysia, since the number of keris maker is getting lesser year by year. Therefore, studying and documenting keris-related matters such as its fabrication and preservation methods are very essential for our future generation. This works thus intends to comprehensively study and document the heritage keris fabrication process and to investigate the mechanical properties of the keris blade in Malaysia including its microstructures, element compositions, tensile strength and hardness. The information on keris fabrication method and preservation was gathered by conducting an interview and sites visit to existing traditional workshops as well as laboratory works. The analysis of keris blade were done using Electron probe micro analysis (EPMA), X-ray diffraction (XRD), Energy dispersive analysis of X-rays (EDAX), Vickers Hardness and Tensile testing machine. It was found that keris blade mainly consist of iron and contained 2.99% of carbon with complex microstructures composing of laminated metal composite (LMC) structure. The presence of oxide dispersion strengthening (ODS) layer at the interface of LMC as well as pearlite structure in keris blade had formed a laminated metal matric composite and improved its tensile strength up to 52.6% higher than cast iron. Besides, it was found that the yield strength was almost the same as compared with 1.0% carbon mild steel. The study also showed that keris blade had a variation of hardness and certain degree of flexibility. Apart from that, this work also focused on the corrosion behaviour of keris blade in coconut water (CW), a traditional method in inhibiting keris blade. Through Tafel and Electrochemical Impedance Spectroscopy (EIS) analysis, the study showed that CW formed passivation with the highest IE of 92% as compared to American Society for testing and Materials (ASTM) water. Coconut water treatment consistently showed an improvement as compared to other inhibitors such as tartaric acid. CW also displayed protective abilities that exceeded both ascorbic and tartaric acid. The hydrophobicity coating materials were evaluated in this work through contact angle measurement and give 112 degrees compared to uncoated sample with 60 degrees. Apart from coating, this work also evaluated a new approach in corrosion protection. The Impressed current cathodic protection (ICCP) showed a linear significant increase of weight gain for 48 hours of exposure time. The difference of mass gain between sample with biased and unbiased current is 95% and increase up to 150%. The result showed that both corrosion protection techniques have a potential to be used in museum environment. These findings thus would give a new insight in the understanding and appreciating Keris as part of Malay civilization.